2014
DOI: 10.1074/jbc.m113.495499
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Abatement of Striatal Dopaminergic Transmission by Cocaine and Methylphenidate

Abstract: Background:The dopamine transporter (DAT) regulates the outflow of dopamine from synapses. Results: We present evidence that the DAT blockers cocaine and methylphenidate increase or reduce the release of DA in the striatum. Conclusion:The reducing effects on DA release are not dependent on a typical blockade of DAT. Significance: The paradoxical blunting of dopamine (DA) release could account for differential effects of psychostimulants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…8D). Previous research has demonstrated that the effects of cocaine on DA uptake and release are mediated through independent mechanisms (Federici et al, 2014; Venton et al, 2006). Consequently, we verified that changes in cocaine’s effect on DA uptake and release were altered independently by analyzing the relationship between cocaine-induced DA uptake inhibition ( K i ) and DA release (Calipari et al, 2015).…”
Section: 0 Resultsmentioning
confidence: 99%
“…8D). Previous research has demonstrated that the effects of cocaine on DA uptake and release are mediated through independent mechanisms (Federici et al, 2014; Venton et al, 2006). Consequently, we verified that changes in cocaine’s effect on DA uptake and release were altered independently by analyzing the relationship between cocaine-induced DA uptake inhibition ( K i ) and DA release (Calipari et al, 2015).…”
Section: 0 Resultsmentioning
confidence: 99%
“…However, the current work provides initial evidence for a possible mechanism by which cocaine reinforcement is increased in SI animals, specifically the differences observed in NAc dopamine release across all cocaine concentrations. In addition to cocaine’s direct effects on DAT-mediated uptake, there are also many other direct and indirect effects that may influence dopamine transmission, including increased D2 autoreceptor activity (Gantz et al, 2013), voltage gated Na+ channel blockade (Wang, 1988), synapsin dependent dopamine pool mobilization (Venton et al, 2006; Kile et al, 2010; Federici et al, 2014) and heterosynaptic activity from feedback circuits to name a few (Zhang and Sulzer, 2012; Ferris et al, 2013). Considering these many effects of cocaine, it is difficult to know what differences between SI and GH rats may be driving greater cocaine-induced release in the NAc of SI rats.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, DAT inhibition by cocaine in PC12 cells causes a concentration-dependent decrease DA released per quantal event [379]. Evoked striatal DA release can also be decreased by sufficiently high concentrations of cocaine and methylphenidate [380]. In PC12 cells, this is not due to an inhibitory effect of D2 autoreceptor activation on quantal size from elevated [DA] o , as the effect of cocaine is unaltered by sulpiride, a D2-receptor antagonist [381].…”
Section: Dopamine Uptakementioning
confidence: 99%